2000
DOI: 10.1007/pl00008666
|View full text |Cite
|
Sign up to set email alerts
|

Identification by RNA fingerprinting of genes differentially expressed during the development of the basidiomycete Lentinula edodes

Abstract: As part of an ongoing project to understand the molecular mechanisms of fruit body development in Lentinula edodes (Shiitake mushroom), RNA fingerprinting by arbitrarily primed PCR (RAP-PCR) was used to identify differentially expressed genes in RNA populations from four stages of L. edodes development vegetative mycelium, primordium, young fruit body and mature fruit body. From 30 RNA fingerprints, we cloned and sequenced 33 RAP fragments after their differential expression patterns had been verified by rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 55 publications
0
46
0
3
Order By: Relevance
“…Forty-one transcripts showed striking up-regulation at either of the developmental stages, suggesting that the corresponding proteins are directly implicated in the morphogenesis and functioning of fruit bodies during spore maturation. In Lentinula edodes (19), A. bisporus (8), and A. aegerita (32), similar numbers of fruit body-regulated genes were identified. Sixteen genes, mostly coding for unknown proteins, had lower transcript concentrations and probably represented vegetative mycelium-specific genes.…”
Section: Discussionmentioning
confidence: 87%
“…Forty-one transcripts showed striking up-regulation at either of the developmental stages, suggesting that the corresponding proteins are directly implicated in the morphogenesis and functioning of fruit bodies during spore maturation. In Lentinula edodes (19), A. bisporus (8), and A. aegerita (32), similar numbers of fruit body-regulated genes were identified. Sixteen genes, mostly coding for unknown proteins, had lower transcript concentrations and probably represented vegetative mycelium-specific genes.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, we screened dioxin-mediated stress response genes to better understand the cellular response of P. chrysosporium utilizing a DDRT-PCR technique. Recently, a successful application of this technique to study fungal cellular response was reported [10,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…About 20 ”g of each sample was separated on a 1.0% denaturing agarose-formaldehyde gel, transferred onto a Hybond-N + nylon filter (Amersham Biosciences) and then fixed by UV cross-linking (Stratagene) (Leung et al 2000). The cDNA probe corresponding to Po.hyd was prepared using the random priming procedure (Megaprime DNA labeling System, Amersham Biosciences).…”
Section: Rna Isolation and Northern Blotmentioning
confidence: 99%